2017
DOI: 10.1007/s00414-017-1531-8
|View full text |Cite
|
Sign up to set email alerts
|

What are the differences in injury patterns of young and elderly traffic accident fatalities considering death on scene and death in hospital?

Abstract: Older traffic participants have higher risks of injury than the population up to 65 years in case of comparable road traffic accidents and further, higher mortality rates at comparable injury severities. Rib fractures as risk factors are currently discussed. However, death on scene is associated with hardly survivable injuries and might not be a matter of neither rib fractures nor age. As 60% of traffic accident fatalities are estimated to die on scene, they are not captured in hospital-based trauma registries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
3
11
0
1
Order By: Relevance
“…It was reported in the literature that traffic accidents occurred mostly on holidays, in summer months and between 18.01-00.00 (14,19,21). In the present study, 39,7% (n=164) of the cases died between 06.00 and 12.00 (P<0,001); and 41,7% (n=172) died in summer, (P<0,001).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It was reported in the literature that traffic accidents occurred mostly on holidays, in summer months and between 18.01-00.00 (14,19,21). In the present study, 39,7% (n=164) of the cases died between 06.00 and 12.00 (P<0,001); and 41,7% (n=172) died in summer, (P<0,001).…”
Section: Discussionsupporting
confidence: 55%
“…Etehad et al conducted a study and reported that 40.5% of the elderly who were injured in traffic accidents were injured when they were pedestrians (6). In a study which was conducted in Germany, it was reported that 57% of the cases that died in traffic accidents were pedestrians (21). In the present study, it was determined that 65.9% of the cases were pedestrians during the accidents.…”
Section: Discussionmentioning
confidence: 45%
“…All three of these articles did not define injury patterns. Of 309 cases in a study published in 2017, the most common combination of injuries were head and thorax injury (45). Injuries described from this more recent publication were less reflective of the modern vehicle fleet because the database comprised road traffic fatalities who died in 2004 and 2005.…”
Section: Study Periodmentioning
confidence: 99%
“…Heinrich et al studied 309 cases who died in 2004 and 2005 and had postmortem examinations. They wrote that postmortem computed tomography (CT) imaging was not done routinely during the study period; therefore, certain injuries to the facial bones, spine, pelvis, and extremities may have been underrepresented in the study (45).…”
Section: Sample Size and Originmentioning
confidence: 99%
See 1 more Smart Citation